Water, creativity and meaning multidisciplinary understandings of human-water relationships - Roberts, Liz (Elisabeth); Phillips, Katherine, 1980- (Earthscan studies in water resource management., 2019)
This volume brings together diverse approaches to exploring human relationships with the watery world and the other living things that rely upon it. Through exploring multiple creative ways of engaging with water and people, the volume adds to the current zeitgeist of writing about water by expanding thediscussion about this vital substance and how, as humans, we relate to it.Chapters focuson creative explorations and explorations of creativity in relation to developing these understandings, including concepts such as hydrocitizenship and responses to drought and flooding. Drawing on the in-depth research and experience of arts practitioners including participatory artists, as well as academics from a variety of fields including geography, anthropology, health studies and environmental humanities, the book provides a rich and multidisciplinaryperspective onwater and creative ways of engaging and understanding human-water relationships.It representsa valuablesource and inspirationfor academics, arts practitioners and those involved in environmental policy and governance